Ex Vivo Expansion of Murine MSC Impairs Transcription Factor-Induced Differentiation into Pancreatic β-Cells - Dario Gerace; Rosetta Martiniello-Wilks; Rosaline Habib; Binhai Ren; Najah Therese Nassif; Bronwyn Anne O’Brien; Ann Margaret Simpson (Stem Cells International)
Combinatorial gene and cell therapy as a means of generating surrogate β-cells has been investigated for the treatment of type 1 diabetes (T1D) for a number of years with varying success. One of the limitations of current cell therapies for T1D is the inability to generate sufficient quantities of functional transplantable insulin-producing cells. Due to their impressive immunomodulatory properties, in addition to their ease of expansion and genetic modification ex vivo, mesenchymal stem cells (MSCs) are an attractive alternative source of adult stem cells for regenerative medicine. To overcome the aforementioned limitation of current therapies, we assessed the utility of ex vivo expanded bone marrow-derived murine MSCs for their persistence in immune-competent and immune-deficient animal models and their ability to differentiate into surrogate β-cells. CD45-/Ly6+ murine MSCs were isolated from the bone marrow of nonobese diabetic (NOD) mice and nucleofected to express the bioluminescent protein, Firefly luciferase (Luc2). The persistence of a subcutaneous (s.c.) transplant of Luc2-expressing MSCs was assessed in immune-competent (NOD) (n=4) and immune-deficient (NOD/Scid) (n=4) animal models of diabetes. Luc2-expressing MSCs persisted for 2 and 12 weeks, respectively, in NOD and NOD/Scid mice. Ex vivo expanded MSCs were transduced with the HMD lentiviral vector (MOI = 10) to express furin-cleavable human insulin (INS-FUR) and murine NeuroD1 and Pdx1. This was followed by the characterization of pancreatic transdifferentiation via reverse transcriptase polymerase chain reaction (RT-PCR) and static and glucose-stimulated insulin secretion (GSIS). INS-FUR-expressing MSCs were assessed for their ability to reverse diabetes after transplantation into streptozotocin- (STZ-) diabetic NOD/Scid mice (n=5). Transduced MSCs did not undergo pancreatic transdifferentiation, as determined by RT-PCR analyses, lacked glucose responsiveness, and upon transplantation did not reverse diabetes. The data suggest that ex vivo expanded MSCs lose their multipotent differentiation potential and may be more useful as gene therapy targets prior to expansion.